Spectroscopic studies of oligostilbenes from Malaysian dipterocarpaceae / Wan Zuraida Wan Mohd Zain ... [et al.] - Wan Mohd Zain, Wan Zuraida; Latip, Jalifah; M. Syah, Yana; Mat So 'ad, Siti Zaiton (Universiti Teknologi MARA Cawangan Pahang, 2007)
Oligostilbenoid compounds derived from stilbenes are found to be the major constituents of Dipterocarpaceae. These oligostilbenes comprise of a series of oligomers such as resveratrol dimers, trimers, tetramers, hexamers, and octamers. This paper, reports the structural elucidation of oligostilbenes from one of the Malaysian Dipterocarpaceae species.